The curious case of a paraspinal mass - Nair, Anand P.; Abraham, Tinu Ravi; Erubothu, Alekhya (International Surgery Journal, 2025)
Chordomas are rare, slow-growing malignant neoplasms arising from embryonic notochord remnants, most commonly found in the sacrococcygeal region and skull base. Cervical chordomas are exceptionally rare, accounting for only 6% of cases. We present a case of a 64-year-old man with cervical chordoma at the C5 vertebral level, manifesting as cervical myelopathy with limb numbness and bowel/bladder dysfunction. MRI and CT angiogram revealed a well-lobulated, lytic mass involving C5–C6, with encasement of bilateral vertebral arteries. Initially suspected as a metastatic lesion, surgery was undertaken without biopsy due to high risk of neurovascular injury. A C4–C6 corpectomy and tumor resection were performed via an anterior transcervical approach. Histopathology and immunohistochemistry confirmed the diagnosis of chordoma. Postoperative recovery was uneventful, with improved neurological status and no recurrence on follow-up MRI at 12 months. Chordomas can mimic other spinal lesions radiologically, complicating diagnosis. MRI, especially with gadolinium contrast, remains the imaging modality of choice. Treatment involves radical surgical resection, which is the most significant prognostic factor, often supplemented by adjuvant radiotherapy. Due to their resistance to conventional chemotherapy and high recurrence rates, emerging therapies such as tyrosine kinase inhibitors and molecular targeted agents (e.g., imatinib, sorafenib) are under investigation. Despite advancements, management remains challenging due to proximity to critical structures and limited systemic therapy options. Multidisciplinary planning is essential for optimal outcomes. This case highlights the diagnostic and therapeutic complexities of cervical chordoma and underscores the importance of individualized, team-based treatment approaches.